Finitude in Maurice Blondel: The Infinite and the Metaphysics of Death - Emma-Adamah, Victor (Journal for continental philosophy of religion, 2022)
The thought of Maurice Blondel has been read (representatively by Emmanuel Falque) as the theological aspirational movement of human action towards the divine, and therefore as the pre-emptive presence of the infinite to human experience. In this reading, absent has been the appreciation of an original Blondelian account of finitude as the essential experience of a human being-toward-death. Against this approach, this essay explores Blondel’s notion of human finitude as a ‘metaphysical experience’ of the existentially revelatory function of death. To this extent, Blondel’s account of finitude positions the philosopher of Aix, beyond the usual contexts of twentieth-century Catholic apologetic philosophy, squarely within Continental philosophical proposals of finitude as seen in Heidegger, Foucault, and Deleuze. Blondel brings to prominence a French Spiritualist account of the positive value of endurance and resistance against death as the revelatory site of a finitude that is neither determined by an a priori closed boundary nor theologically overdetermined as an aspiration to the infinite.